2022
DOI: 10.3389/fpsyt.2022.856998
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Resilience: A Narrative Review

Abstract: Resilience refers to the adaptability of a person – an ability to “bounce-back” from stressors. We question if resilience can be strengthened, potentially to decrease the risk of stress-related disorders. Unfortunately, the molecular origins of resilience are complicated and not yet well understood. In this review, we examine the various physiological biomarkers of resilience, including the associated genes, epigenetic changes, and protein biomarkers associated with resilient phenotypes. In addition to assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 112 publications
(157 reference statements)
1
9
0
Order By: Relevance
“…Other approaches assume that resilience is continuously distributed and model resilience in terms of deviation from what is expected relative to trauma exposure status [ 28 , 29 ]. However, congruence across approaches is not commonly investigated, resulting in limited comparability across studies and settings [ 21 , 30 , 31 ]. Additionally, given the narrow focus on psychological functioning and internalizing disorders in the extant literature, individuals who may be asymptomatic in some domains of well-being, but struggling to adjust to loss in other unmeasured domains, are not typically identified [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches assume that resilience is continuously distributed and model resilience in terms of deviation from what is expected relative to trauma exposure status [ 28 , 29 ]. However, congruence across approaches is not commonly investigated, resulting in limited comparability across studies and settings [ 21 , 30 , 31 ]. Additionally, given the narrow focus on psychological functioning and internalizing disorders in the extant literature, individuals who may be asymptomatic in some domains of well-being, but struggling to adjust to loss in other unmeasured domains, are not typically identified [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCP1 or monocyte chemoattractant protein 1, is a known proinflammatory chemokine that recruits leukocytes including monocytes, dendritic cells and memory T cells to sites of inflammation. More specifically, MCP1 may play a role in the ability of astrocytes to recruit peripheral monocytes during the stress response ( 24 ). In a recent published review, MCP1 was mentioned as a marker associated with low resilience to stress, specifically, the salivary level of MCP1 was found to be correlated with PTSD associated symptoms in multiple studies ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, MCP1 may play a role in the ability of astrocytes to recruit peripheral monocytes during the stress response ( 24 ). In a recent published review, MCP1 was mentioned as a marker associated with low resilience to stress, specifically, the salivary level of MCP1 was found to be correlated with PTSD associated symptoms in multiple studies ( 24 ). Lower levels of MCP1 have been found to be associated with greater happiness during acute stress ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60–70% of PTSD-related psychological and physiological disorders do not develop or subside within 1–4 weeks [ 17 ]. The long-term response to severe stress apparently depends on individual vulnerability or resilience [ 17 , 18 , 19 ]. Recently, we compared the effects of PS on the heart of rats segregated into groups susceptible or resilient to experimental PS and showed that following PS, morphological cardiac injury, ECG changes, and impaired exercise tolerance were more pronounced in PS-susceptible (PSs) rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%